Discovery of Cymopolyphenols A–F From a Marine Mesophotic Zone Aaptos Sponge-Associated Fungus Cymostachys sp. NBUF082 - Wang, Tingting; Zhou, Jing; Zou, Jiabin; Shi, Yutong; Zhou, Wenli; Shao, Peng; Yu, Tianze; Cui, Wei; Li, Xiaohui; Wu, Xingxin; Ye, Jing; Yan, Xiaojun; et al. (Frontiers in Microbiology, 2021)
Mesophotic coral ecosystems (MCEs) have complex but understudied biodiversity, especially for natural products discovery. Untargeted metabolomics research on 80 extracts prepared from marine sponge-associated fungi, half from shallow reefs (<30 m) and half from MCEs (30−150 m), facilitated prioritization for further study a Cymostachys fungus from a 103 m deep Aaptos sponge. LC-MS target-directed isolation yielded a series of new compounds, cymopolyphenols A-F (1−6), and two known phenylspirodrimanes, F1839-I (7) and stachybotrylactone (8). This is the first report of natural products from the recently described genus, Cymostachys. Compounds 1−6 and 8 contain a dihydroisobenzofuran moiety, and 4−6 are low-order polymers of 1 with novel scaffolds. The structures of the compounds were established by spectroscopic and spectrometric data interpretation, with further support from X-ray crystallography studies of 3 and 4. Compound 3 undergoes facile racemization in solution, and was found to crystalize as a racemic mixture. Compound 5 was also obtained in racemic form, and after chiral chromatography, both separated enantiomers racemized in solution by a presumed keto-enol tautomerization. Compounds 1 and 3−6 were found to be weakly antimicrobial (MIC 16−64 μg/mL) in vitro against several Gram-positive and Gram-negative human or aquatic pathogens, compound 5 was shown to chelate iron in vitro at 10 μM, and 8 activated plant disease resistance in vivo in a transgenic model organism.